Aesthetic interpretation of waruna symbolism in the colossal dance performance waruna rakta samasta - Kasih, Ni Nyoman; Yulianti, Ni Ketut Dewi (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2025)
This research departs from the lack of scholarly exploration into how mythological figures like Waruna can function as aesthetic sources in contemporary Balinese performing arts. Waruna, known in Hindu-Balinese mythology as the god of water and the ocean, symbolizes cosmic harmony between nature and human life. This study aims to analyze how Waruna’s symbolism contributes to the aesthetic construction of the colossal dance performance Waruna Rakta Samasta, particularly in terms of form, meaning, and presentation. Employing a qualitative method, the research integrates Djelantik’s aesthetic theory focused on form, weight, and appearance, and a hermeneutic approach to interpret symbolic meaning. Data were collected through direct observation of the performance and literature studies. Findings reveal that Waruna's symbolism is not only embodied in visual elements like the Borobudur outrigger boat, lighting, and video mapping, but also in movement and music, producing an immersive maritime experience. The aesthetic is enriched with spiritual and philosophical messages that align with the Balinese Tri Hita Karana values. This study contributes to the development of colossal performing arts in Bali by offering a contemporary reinterpretation of traditional symbols and providing a model for integrating mythological aesthetics into modern performance practice.